The Effect of Environmental, Social, and Governance Disclosure on Firm Value Moderated by Firm Reputation in the Consumer Cyclicals Sector During 2020–2024 - Susan Lalenoh; Rilla Gantino (Indonesian Journal of Taxation and Accounting, 2026)
Purpose - This study aims to examine the effect of Environmental, Social, and Governance (ESG) Disclosure on Firm Value with Firm Reputation as a moderating variable in companies within the Consumer Cyclicals sector listed on the Indonesia Stock Exchange during the 2020–2024 period. The study is motivated by the increasing importance of sustainability disclosure in corporate reporting and the inconsistent empirical findings regarding the relationship between ESG disclosure and market valuation. Methods - Using a quantitative research design, this study employs panel data obtained from annual reports, financial statements, and sustainability reports of 16 firms, resulting in 80 firm-year observations. Firm Value is measured using Price to Book Value (PBV), ESG Disclosure is measured based on sustainability reporting indicators, and Firm Reputation is proxied by the Corporate Image Index (CII) published by Frontier Consulting Group. The data are analyzed using panel data regression with Moderated Regression Analysis (MRA) implemented through STATA software. Findings - The results show that ESG Disclosure and Firm Reputation simultaneously have a positive and significant effect on Firm Value, with the regression model showing a Wald chi-square value of 6424.24 and a probability of 0.0000. Partially, ESG Disclosure has a positive and significant effect on Firm Value (β = 1.7108; p = 0.001), while Firm Reputation also demonstrates a positive and significant influence (β = 1.0053; p = 0.000). Furthermore, the interaction term between ESG Disclosure and Firm Reputation is positive and significant (β = 0.6713; p = 0.016), indicating that Firm Reputation strengthens the relationship between ESG Disclosure and Firm Value. Research Implication - The findings imply that sustainability disclosure becomes more effective in enhancing market valuation when supported by strong reputational capital. However, this study is limited to firms within the Consumer Cyclicals sector and relies on secondary data sources, which may restrict generalizability across industries. Originality - The originality of this study lies in integrating ESG disclosure, reputational capital, and market valuation within a moderating framework in an emerging market context, offering insights for corporate managers and investors in aligning sustainability strategies with long-term value creation.